Plant-mediated interactions: considerations for agent selection in weed biological control programs - Milbrath, Lindsey R.; Nechols, James R. (My University, 2014)
Plant-mediated indirect interactions among herbivores (arthropods and pathogens) are common and extensively reported in the ecological literature. However, they are not well-documented with respect to weed biological control. Such interactions between biological control agents can have net positive or negative impacts on total weed suppression depending on the strength of the interaction(s), the relative importance of the agent indirectly impacted, and the combined weed suppression that results. A better understanding of plant-mediated interactions may improve decision-making about which agents to introduce in classical biological control programs for greatest impact on invasive weeds. This paper reviews the subject, including examples from the biological control literature; outlines the need for research on indirect effects of herbivores on other herbivores; discusses how such knowledge may strengthen classical biological control programs for invasive weeds; and provides recommendations for the kind of studies that should be done and how information about plant-mediated interactions could be integrated into agent evaluation protocols, to assist in decision-making about agents for importation and release.
Keywords: Indirect interactions; Weed biological control; Pre-release evaluation; Agent selection